(3JShjb GdeYdheGJ h NOeGJ GdeYdheGJ (B/s - (3YdjGf, QHMj eUWais; (3GdSGeQGFj, GjeGf aGVds ((3YeGf(B: s (3OGQ UaGA(B, s, 2010)
(3eaGgje CSGSjI aj JShjb GdeYdheGJ , HjFI JShjb GdeYdheGJ , GdJShjb h JShjb GdNOeGJ aj GdeDSSGJ GdeYdheGJjI , JLRFI GdShb GdeSJgOaI h GdeRjL GdJShjbj , GSJQGJjLjI JShjb GdeYdheGJ , GdYdGbGJ GdYGeI aj NOeI GdYedjI GdJShjbjI, GdJShjb YHQ GdGfJQfjJ , HMhK GdJShjb h fXGe GdeYdheGJ GdJShjbj (B.s
(3eQGLY U(B.379s
Keywords: (3GdHK GdEfJbGFj ddeYdheGJs; (3GdeYdheGJs; (3GdecJHGJs; (3NOeGJ GdeYdheGJs